Cognitive IoT : emerging technology towards human wellbeing - Patra, J. P.; Verma, Gurudatta (Boca Raton, FL : CRC Press, 2023)
"This book contains different research areas of Cognitive IoT and explains how Machine learning algorithms can be applied for Cognitive IoT. This book deals with applications of Cognitive IoT in this pandemic (Covid-19), applications for student performance evaluation, for human healthcare for chronic disease prediction, use of wearable sensors and review regarding their energy optimization and how cognitive IoT helps in farming through rainfall prediction, and lake level prediction. Features: Describes how cognitive IoT is helpful for chronic disease prediction and processing of data gathered from health care devices. Explains different sensors available for health monitoring. Explores application of Cognitive IoT in Covid-19 analysis. Discusses pertinent efficient farming applications for sustaining agricultural growth. Review smart education aspects like student response, performance, and behavior, Instructor response, performance, and behavior. This book aims at Researchers, Professionals and Graduate students in Computer Science and Engineering, Computer Applications and Electronics Engineering, Wireless communications, and networking"--
OCLC-licensed vendor bibliographic record.
Keywords: Public health -- Data processing; Internet of things; Soft computing; COMPUTERS / Machine Theory; COMPUTERS / Computer Engineering; MATHEMATICS / General